Annual Plan 1998-99 Maharashtra Part I - Planning Commission (Planning Commission, 1998)
The State of Maharashtra was formed on the 1st May, 1960. The State Government, right from its formation, followed a path of development planning. The planning process in the country started in the year 1951 with the first five year plan. Maharashtra joined this process of social and economic development through planning from third five year plan onwards.
Planning Department, Government of Maharashtra